AGENDA RISET DIGITAL RELIGION DARI PERSPEKTIF KAJIAN MEDIA: SEBUAH TINJAUAN KONSEPTUAL - Widjanarko, Putut; Putut Widjanarko, Putut (Program Studi Ilmu Komunikasi Universitas Paramadina, 2025)
This article examines the conceptual landscape of digital religion studies through the perspective of media and communication research. Over the past two decades, digital religion has developed as an interdisciplinary field that explores how religious practices, identities, communities, and authorities are shaped within the convergence of online and offline spaces. This study employs a conceptual review method, a qualitative approach to literature review in which the researcher surveys various sources related to a perspective or theory and then formulates a conceptual map based on that exploration. The discussion highlights four theoretical frameworks commonly used by scholars with a media studies background: mediatization, mediation, social shaping of technology, and media ecology. Each framework provides a different lens on the interaction between digital media and religious practices—whether emphasizing technological determinism or human agency. The study also maps six key areas of digital religion research: authority, ritual, identity, community, embodiment, and the conceptualization of religion itself. Furthermore, it identifies two major issues for future inquiry. First, the increasingly blurred boundaries between digital and physical spaces call for research on hybrid environments where online and offline religious practices intertwine. Second, the emergence of new technologies such as artificial intelligence, robotics, and immersive virtual reality raises profound ethical and cultural questions regarding the future of religion and human–technology relations. By situating digital religion within the framework of media studies, this article seeks to provide a foundation for scholars, particularly in Indonesia, to contribute to global discourse on religion in the digital era.